Titik Singgung Sengketa Pertanahan di Lingkungan Peradilan Umum, Agama, dan Tata Usaha Negara - Tehupeiory, Aarce (Universitas Proklamasi 45, 2023)
The judiciary courts under the Supreme Court have the authority as stated in Article 25 of Law Number 48 of 2009, which are District Courts, Religious Courts, Military Courts, Administrative Courts. However, there is an intersection of land dispute cases in the General, Religious, and State Administrative courts. Disputes over court decisions include the disputing parties’ inacceptance of the court decision. Court decisions unable to be be executed because the ownership status and owners have changed.The different legal consequences for the dispute object status of the same case will make the case more complicated, the resolution is not fast and the costs are not cheap. So that it is not in accordance with the principle of simple justice, fast and low cost and there are differences in the interpretation. In order to create fair and just law enforcement in Indonesia, namely the existence of the following pillars: Fair and correct law enforcement.The existence of law enforcers with dignity, professionalism, integrity and the creation of a conducive social environment (a society that is aware of the law). With the case and statutory approach method, an agrarian court was formed to resolve disputes related to land cases, its job is not only to examine formal books but material truth by understanding the principles of land tenure and ownership provided for by the national land law. Improving the chamber system in settlement of land cases or disputes.